Efficacy of combined therapy with fenbendazole and Bacillus amyloliquefaciens in treating strongylatosis in horses - O. V. Demkina (Российский паразитологический журнал, 2025)
The purpose of the research is to evaluate the efficacy of the combined use of fenbendazole and Bacillus amyloliquefaciens against Strongylata in horses, to compare the combined therapy to fenbendazole monotherapy, and to study the effect on the general clinical state of horses.Materials and methods. The study was conducted on 20 horses divided into two groups of 10 animals. The horses from the experimental group were given fenbendazole once at a dose of 7.5 mg/kg, and the probiotic B. amyloliquefaciens daily at a dose of 50 mg/kg for 14 days. The control group of horses received only fenbendazole. The therapy efficacy was monitored by examining faeces using the flotation method on days 7, 10, 14, 16, 19, 22, 25, 28, 31, and 34 after treatment. On day 14 of the experiment, the test reduction rates in the number of eggs in faeces were calculated. To determine starting dates of repeated egg release, the values obtained on days 7 and 14 were used. Faecal microbiota was analyzed before the treatment and on day 14.Results and discussion. Both groups of horses showed a reduction in Strongylata eggs in faeces after treatment with a gradual increase in their number by day 34 of the experiment. The first Strongylata eggs were detected on day 7 of the therapy. The period of repeated release of Strongylata eggs was two weeks in the experimental and control groups. Test reduction rates of eggs in faeces were below 90% on day 14 in both groups. The analyzed faecal microbiota did not reveal significant changes after the probiotic, although Aspergillus fungi disappeared in the experimental horses. Throughout the study, the horses in both groups remained clinically healthy with no signs of gastrointestinal disorders. The combined fenbendazole and B. amyloliquefaciens did not result in any statistically significant increase in the deworming efficacy as compared to fenbendazole alone (P > 0.05). However, the combined anthelmintic and probiotic showed a certain biological advantage expressed in a decrease in Strongylata eggs after the treatment in the experimental group. Despite the lack of significant changes in the intestinal microbiota, the absence of Aspergillus spp. after administered probiotic may indicate its potential antifungal effect.